POSSIBILITIES OF PREDICTING THE EFFECTIVENESS OF ANTIHYPERTENSIVE THERAPY IN THE POPULATION OF MOUNTAIN SHORIA - Мулерова, Татьяна Александровна; Морозова, Наталья Игоревна; Алексеева, Наталья Сергеевна; Мулерова, Екатерина Захаровна; Огарков, Михаил Юрьевич (Medicine in Kuzbass, 2025)
Materials and methods. The study involved a population of residents of Mountain Shoria with arterial hypertension (AH): 367 (40.7%) Shors and 230 (45.3%) non-natives. Medical examination was carried out in expeditionary conditions using standard methods. Based on the treatment regimen, 6 observation groups were formed: monotherapy with renin-angiotensin-aldosterone system (RAAS) blockers (35 people), monotherapy with calcium channel blockers (CCB) (38 people), diuretic monotherapy (41 people), a combination of RAAS blockers with CCB (165 people), a combination of RAAS blockers with a thiazide-like diuretic (203 people), a three-component combination (48 people). Polymorphisms of the ACE (rs4340), AGT (rs699), AGTR1 (rs5186), MTHFR (rs1801133) and NOS3 (VNTR) genes were tested using polymerase chain reaction. A comprehensive assessment of risk factors was performed using multivariate logistic regression in the R statistical environment (v.4.3.2, GNU GPL2 license). Results. Belonging to the indigenous ethnic group, regardless of other risk factors and the therapy used, reduced the effectiveness of antihypertensive therapy by 1.8 times [OR = 0.56; 95% CI (0.36-0.87), p = 0.011], the presence of abdominal obesity – by 1.6 times [OR = 0.61; 95% CI (0.38-0.98), p = 0.043]. In patients with hypertension and obesity, a negative effect of the I/I genotype of the ACE gene on the effectiveness of antihypertensive therapy was found [OR = 0.15; 95% CI (0.03-0.53), p = 0.006]. On the contrary, carriage of the homozygous A/A genotype of the AGTR1 gene increased the chances of a positive outcome of therapy, but only in individuals of non-indigenous ethnicity [OR = 4.30; 95% CI (1.54-12.8), p = 0.007]. Conclusion. The pharmacological response to drugs is influenced by various phenotypic and genetic factors that contribute through different points of application.